Inovasi Pelayanan Online Akta Kelahiran di Dinas Kependudukan dan Catatan Sipil - Isma Nirmala (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2022)
The purpose of the study was to determine the innovation of online birth certificate making services as well as the advantages and disadvantages for people in the city of Palembang. The research method uses a qualitative approach with data collection techniques, namely interviews, observation, and documentation. The informants used by the researcher were two Heads of Kelurahan Offices, Three Communities, and Five Employees of the Population and Civil Registration Office of Palembang City using descriptive analysis. The results of the study show that online birth certificate service innovation is a service strategy to make it easier for people to make birth certificates. In terms of time and place, people can register a birth certificate anytime and anywhere. The conclusion of the study shows that online innovation is expected to facilitate the community in making birth certificates. Keywords: Innovation, Online Birth Certificate, Service.